References on the health care for newborns with suspected or actual infection of SARS-CoV-2 - Marisel Armas-López; Niura García-Rivera; Inalkis Shuman-Betancourt; Yadira del Pilar Fong-Berguelich (Revista Información Científica, 2020)
Introduction: differences are revealed concerning the care of the newborn with a positive diagnosis or suspected to be infected with COVID-19.